Evaluasi Aplikasi i-Waris menggunakan Pengujian Usability - Febry Aditya Wibisono Romadhon; Ismiarta Aknuranda; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
i-Waris is an application that provides legacy calculations for users who need it. The downloader's assessment data on the PlayStore application market shows that there are still many users who still question the existing calculations in the i-Waris application because there are many calculations that confuse users. Even though this feature is the main feature of the application, users feel that they are not getting maximum results in this application. Therefore, we evaluate the usability of user convenience and how user interacts with the i-Waris application. To find out the usability conditions used usability testing with a qualitative approach, which provides 17 task scenarios and in each scenario there is a SEQ (Single Ease Question) questionnaire from the results of the SEQ questionnaire in the i-Waris application getting an average value of 3.2 which means it is in the difficult category. . From usability testing with 17 task scenarios, new problems are found in the i-Waris application. The results of interviews and observations indicate that the i-Waris application still has many problems and lacks the information required by users, for example the inaccessible â€œaboutâ€ page and explanation of calculation results that do not exist on the mobile application. The problems found in the i-Waris application are 33 problems. Therefore, it is necessary to fix the i-Waris application to solve existing problems such as fixing the